PENATALAKSANAAN FISIOTERAPI PADA HERNIA NUCLEUS PULPOSUS (HNP) DENGAN MODALITAS TRAKSI DAN MC. KENZIE EXERCISE DI RSO PROF DR. R. SOEHARSO SURAKARTA - Octaviani Rizky Widyasari; Irine Dwitasari Wulandari (LPPM Universitas Pekalongan, 2020)
Hernia Nucleus Pulposus (HNP) is a disease where the part of the nucleus is made of a gel-shaped material in the spinal cord coming out of the annulus resulting in suppression or narrowing of the spinal nerves and causing pain. Physiotherapy problems are the presence of pain, spasm, limited range of joint motion, decreased muscle strength and decreased functional activity. To determine the effect of Physiotherapy Management on the condition of HNP with modalities traction and mc kenzie exercise. The study was conducted at the Rso Prof Dr. R. Soeharso Surakarta with descriptive analytic research design. Based on the therapy, the following results were obtained: (1) The decrease in silent pain T1=2 to T4=0, tenderness T1= 4 to T4= 2, motion pain T1=6 to T4=3 (2) The decrease in spasm at T4 = 0, ( 3) There is an increase in the scope of motion of trunk joint flexion T1=4cm to T4=14cm, extension T1 = 3cm to T4 = 6cm, lateral flexi dextra T1 =14cm to T4 =18cm, lateral flexi left T1 = 12cm to T4 = 16cm and rotation T1 = 35°-0°-35° to T4 =45°-0°-45° (4) There is an increase in trunk muscle strength, flexor T1=4 becomes T4=5, extensor T1= 4 becomes T4 =4+, Lateral Flexor T1=4 becomes T4=5, and rotator T1 = 4 becomes T4=5 (5) There is a decrease in disability T1=46% to T4=20%. Physiotherapy interventions with modalities traction and mc. Kenzie exercise can reduce problems arising in the condition of the HNP.